Author Correction: Perceived stress and non-alcoholic fatty liver disease in apparently healthy men and women - Danbee Kang; Di Zhao; Seungho Ryu; Eliseo Guallar; Juhee Cho; Mariana Lazo; Hocheol Shin; Yoosoo Chang; Eunju Sung (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.